Avaliação crítico-emancipatória: desafios para a prática docente em uma escola do campo - Berger, Natieli Dalleprane (2021)
This research aims at proposing a way to build the evaluation of the teaching-learning process in the context of a rural school, based on a critical-emancipatory perspective. For justify the research, we dialogued with some concepts that served as theoretical proposes for the study's foundation, such as evaluation, theoretical conceptions of evaluation, external evaluations, emancipatory education, evaluation in a critical-emancipatory perspective, Rural Education, among other critics that was necessary to we could understand and catch a glimpse of ways to build the evaluation in the context of Rural Education, based on this perspective. The theoretical-methodological approach was characterized by a qualitative participant research, enabling the involvement of educators from the rural school in the analysis of their own reality and practice, developing from the interaction between the researcher and members of the investigated situations. This way, the research subjects were the teachers who attend the 6th to 9th grade classes of EMEIEF São Sebastião from the set of municipal schools of Santa Maria de Jetibá/ES. The research reaffirm the need to reflect critically on the evaluation practices prevalent in rural schools, which are influenced and penalized by external evaluations that segregate rural peoples and indicated the need to develop studies and practices on the evaluation of these institutes, strengthening how struggles of rural subjects for a liberating education. From this process emerged, as from theoretical research as the intervention realized, a critical-emancipatory evaluation of the teaching-learning process emerged. The product introduced is itself formation that was developed and its structure, which shows itself as inspiring possibilities of other evaluate practices committed to liberating education.